(3TQM fLGI GdYHGOs - (3GdfLaj, YHGS Hf MSf Hf LYaQ cGTa GdZWGA, J (B1323(3g`s
(3ChdgG (B:s
(3YedG HYehe eG bVi(B... (3EdG EPG GeJfY GdJMjV Hg TQYG(B...s
(3BNQgG (B:s
(3ddaQb Hjf SYI GdeGA hchfg(B... (3dSYJg gfG gj GdTQYjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B30s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B30s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis